Monitoring and privacy in automobile insurance markets with moral hazard - Lilia Filipova (Universität Augsburg, Institut für Volkswirtschaftslehre, 2007)
This paper considers moral hazard insurance markets when voluntary monitoring technologies are available and insureds may choose the precision of monitoring. Also privacy costs incurred thereby are taken into account. Two alternative contract schemes are compared in terms of welfare: (i) monitoring conditional on the loss with only the insurance indemnities based on the monitoring data, and (ii) unrestricted monitoring with both the premiums and the indemnities depending on the data. With any contract scheme some monitoring will be optimal unless the privacy costs increase too fast in relation to the precision of the monitoring signal. In the benchmark situation (without privacy costs) relying completely on both signals (monitoring and the outcome) informative of effort (ii) maximizes welfare. In the presence of privacy costs, the contract with conditional monitoring (i) might dominate the contract which fully includes the outcome and the monitoring signal into the sharing rule (ii). Apart from the direct effect of restricting privacy costs only to the state of loss, there are also an additional indirect incentive and a risk-sharing effect with this contract. Letting the individuals choose the precision of the monitoring technology at the time they reveal the data (ex post) is inefficient with either contract scheme.
urn:nbn:de:bvb:384-opus4-711438
Keywords: D82; G22; 330; moral hazard; conditional monitoring; value of information; privacy; Kraftfahrtversicherung; Moral Hazard; Kontrolle; Datenschutz; Kosten; Versicherungsökonomik; Vertragstheorie; Theorie